Coulomb drag and depinning in bilinear Josephson junction arrays. (28th September 2017) - Wilkinson, Samuel A; Vogt, Nicolas; Cole, Jared H
Abstract: Coulomb drag and depinning are electronic transport phenomena that occur in low-dimensional nanostructures. Recently, both phenomena have been reported in bilinear Josephson junction arrays. These devices provide a unique opportunity to study the interplay of Coulomb drag and depinning in a system where all relevant parameters can be controlled experimentally. We explain the Coulomb drag and depinning characteristics in the I – V curve of the bilinear Josephson junction array by adopting a quasicharge model which has previously proven useful in describing threshold phenomena in linear Josephson junction arrays. Simulations are performed for a range of coupling strengths, where numerically obtained I – V curves match well with what has been previously observed experimentally. Analytic expressions for the ratio between the active and passive currents are derived from depinning arguments. Novel phenomena are predicted at voltages higher than those for which experimental results have been reported to date.